Mathematical Literacy Ability in HOTS (High Order Thinking Skills) Problem Solving of Class VIII Students - Muhammad Iqbal; M. Turmuzi; Junaidi; Laila Hayati (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aimed to find out and describe the mathematical literacy ability of class VIII students of SMP Negeri 7 Mataram for the 2022/2023 academic year in solving HOTS problems. Therefore the type of research used is descriptive research. The sample in this study was students of class VIII SMP Negeri Mataram. The sampling technique used was purposive sampling with a sample of 80 people. Data collection uses written test techniques in descriptions declared valid and feasible. Data collection was carried out directly and implemented by the school. The appropriate question descriptions are given to students to solve so that data on the scores of students' answers in answering the descriptions of HOTS questions and the level of mathematical literacy are obtained. After the data collection of students' answer scores is completed, the data is examined. The data that has been examined is then processed, tabulated, grouped, and analyzed to obtain research results that show that students have not been able to reach level 4 as much as 12.5%. Students who can reach level 4 are only 37.5%, while for levels 5 and 6, only 36.25% and 13.75%, respectively, for the level of mathematical literacy ability of class VIII students of SMPN 7 Mataram for the academic year 2022/2023 in solving HOTS problems the majority are high and very high with 43.75% and 48, 75%. Thus, the higher the problem-solving ability of students, the higher the level of literacy that can be achieved.